Systematic Literature Review on Developing an Integrated STEM Leadership Model for Middle Leaders in School - Rahman, Saifulbahri Abdul; Busari, Abdul Halim; Mazlan, Mohammad Nur Azhar; Suhaili, Adawati (Institute of Advanced Engineering and Science, 2025)
This systematic literature review investigates the development of anintegrated science, technology, engineering, and mathematics (STEM)leadership model tailored for middle leaders in Malaysian schools. Theintroduction highlights the global emphasis on STEM education to fosterinnovation and economic growth, while acknowledging Malaysia’scommitment to enhancing STEM capabilities within its educational system.The problem statement identifies a gap in effective STEM leadership amongmiddle leaders, which is critical for implementing STEM initiatives andimproving student outcomes. To achieve this, we conducted an extensivesearch of scholarly articles from reputable databases such as Scopus and Webof Science (WoS), focusing on studies published between 2021 and 2024. Theflow of study is based on PRISMA framework. The database found (n=34)final primary data was analyzed. The finding was divided into three themeswhich are i) STEM education policy and implementation; ii) leadership inSTEM educational; iii) professional development in STEM education. Theconclusion emphasizes the need for a specialized leadership model thatincorporates instructional leadership principles, fosters professionaldevelopment, and supports collaborative practices among middle leaders. Thisintegrated model aims to address the unique challenges faced by middleleaders in Malaysian schools, ultimately enhancing STEM education andcontributing to Malaysia’s educational and economic aspirations.